Multi-Category Competition and Market Power: A Model of Supermarket Pricing - Thomassen, Øyvind; Smith, Howard; Seiler, Stephan; Schiraldi, Pasquale (American Economic Review, 2017)
In many competitive settings, consumers buy multiple product categories, and some prefer to use a single firm, generating complementary cross-category price effects. To study pricing in supermarkets, an organizational form where these effects are internalized, we develop a multi-category, multi-seller demand model and estimate it using UK consumer data. This class of model is used widely in theoretical analysis of retail pricing. We quantify cross-category pricing effects and find that internalizing them substantially reduces market power. We find that consumers inclined to one-stop (rather than multi-stop) shopping have a greater pro-competitive impact because they generate relatively large cross-category effects. (JEL D12, L11, L13, L81)